A facile organosilane-based strategy for direct synthesis of thin MWW-type titanosilicate with high catalytic oxidation performance. Issue 23 (17th October 2018) - Jin, Shaoqing; Tao, Guiju; Zhang, Shilin; Luo, Yi; Fu, Wenhua; Wang, Zhendong; Gao, Huanxin; Sun, Hongmin; Yang, Weimin
Abstract : A facile organosilane-based synthetic strategy was successfully developed to prepare thin Ti-MWW zeolite with high catalytic oxidation performance. Abstract : Although numerous strategies have been developed to improve the diffusion and catalytic activity of MWW-type titanosilicate (Ti-MWW zeolite) in oxidation of bulky molecules, preparation of Ti-MWW zeolite with high external specific surface area (SSA) by a simple and efficient method is still highly required. Herein, a facile organosilane-based synthetic strategy was successfully developed to prepare thin Ti-MWW zeolite with a thickness of 15 ± 5 nm and an external SSA as high as about 210 m 2 g −1 . Moreover, based on the structural characterization, the synthesis mechanism of the thin Ti-MWW zeolite was discussed in detail. Importantly, due to more framework TiO4 species and their better accessibility, the obtained thin MWW-type titanosilicate showed superior catalytic performance in epoxidation of bulky olefins than conventional Ti-MWW zeolite. It is believed that this facile organosilane-based synthetic strategy can be used in the development of other highly efficient layered zeolite catalysts.